Group identification in the context of global virtual teams - Anttonen, Milla (fi=Turun yliopisto|en=University of Turku|, 2018)
This study explores group identification in global virtual teams that are characterized by the aspects of geographical dispersion, cultural diversity and reliance on information and communication technology. The purpose of this research is to discover how group identification is constructed and sustained in global virtual teams and to explore how the above three aspects of global virtual teams reflect on group identification. The theoretical background of this study is constructed on current literature on topics of identification and global virtual teams. This study uses a qualitative research method for conducting the empirical research. The method of the study consists of the instrumental case study method with two case teams selected from an established multinational B2B-company. The two teams are partly virtual and partly local by nature and are each situated from 2-3 different locations and in total on 3 different continents. The collection of empirical data was carried out through 9 qualitative, semi-structured interviews that were conducted between January and February 2017 in one-on-one virtual meetings via Skype For Business. Interview participants were employees in the two virtual teams except for one team leader. Thematic analysis was used to categorize and interpret the interview data and provide the basis for the analytical framework. The results largely support the findings of extant literature but also provide further insights about group identification in global virtual teams. It is suggested that creating and sustaining group identification in global virtual teams can be significantly slower and more challenging than in traditional face to face teams due to the variety of dimensions within global virtual teams that can affect on group identification. However, group identification in global virtual teams does occur and managing it is feasible and to a large extent essential in order to support teams that are otherwise at the risk of suffering from the distance and isolation between its team members. As a result, as long as the potential influence of the team dispersion, virtual communication, and cultural diversity is identified and actively managed within global virtual teams, the risks to group identification can be reduced, and in fact, group identification can be stimulated and supported in globally distributed teams. All in all, this study provides new inputs to the theoretical framework with the support of the findings that emerged from the empirical data. Future research, however, is necessary in order to explore identification in teams with a more flexible membership or with team members that are more interdependent in their work.